Crescimento inicial de mamoeiro micorrizado e irrigado com águas de diferentes salinidades - Oliveira Filho, Francisco de Sales (Universidade Federal Rural do Semi-Árido, 2019)
Irrigation of seedlings of fruit species with low quality water, especially with high salt content, is a reality among Brazilian semi-arid seedling producers, which is a condition that negatively impacts the quality of plants in their initial phase of growth. It is necessary to make use of strategies that enable the use of these waters without compromising the quality of the seedlings. In this sense, the objective of the present study was to evaluate the effect of mycorrhization on the morphophysiology of Papaya (Carica papaia L.) seedlings of the Formosa Group, Tainung 1 Hybrid, submitted to saline irrigation. The research was conducted at the seedling production nursery of the Instituto Federal de Educação, Ciência e Tecnologia da Paraiba - IFPB, Campus Sousa, from March to December 2018. The experimental design was a randomized complete block design, in a 4 x 5 factorial arrangement, referring to the species of fungi Gigaspora candida, Acaulospora scrobiculata, Dentiscutata heterogama and without mycorrhizas and, at water salinity levels, 0.0; 10.0; 20.0; 30.0 and 40.0 mmolc L-1, in four repetitions. The inoculum of mycorrhizal fungi came from the culture collection of Embrapa Agrobiologia, Seropédica-RJ. The inoculation occurred at sowing time, using a soil mixture containing spores, hyphae and colonized roots, with the fungi of the studied mycorrhizal species. Irrigations with saline water were performed daily to leave the soil with moisture close to the maximum retention capacity, based on the weighing method, and the weekly 20% leaching fraction was applied. The characteristics evaluated were: percentage of mycorrhizal colonization, relative water content, water saturation deficit, membrane damage, photosynthetic pigments, leaf area, physiological indexes, biometrics, dry matter mass accumulation in root, stem, leaf and total, accumulation of nitrogen, phosphorus, potassium and calcium macronutrients and sodium and chloride ions in leaf tissue. Higher percentage of mycorrhizal colonization was evidenced by Dentiscutata heterogama and Gigaspora candida, regardless of salt concentration. However, it was found that the rate of mycorrhizal infection decreased with increasing salinity. Improvements in relative water content, photosynthetic pigment concentration, physiological indices, biomass accumulation, growth, concentration and nutrient accumulation were evidenced in mycorrhized papaya seedlings for all salt concentrations. In general, the use of mycorrhizae provided higher quality non-mycorrhized papaya seedlings regardless of the saline water level. Dentiscutata heterogama and Gigaspora candida species were recommended because of the significant relief of the deleterious effect of salinity on the morphophysiological components of papaya seedlings
Keywords: Carica papaia L.; Salinidade; Fungos micorrízicos arbusculares; Endomico; Carica papaya L.; Salinity; Arbuscular mycorrhizal fungi; Endomycorrhizae; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA